Tradisi Petik Laut Sebagai Kearifan Lokal Dalam Konservasi Dan Pengelolaan Sumber Daya Pesisir Gresik - tsaniatul khayati, Tsania (CONSERVA, 2025)
Petik Laut is a local wisdom tradition that has been passed down through generations in the coastal areas of Gresik, particularly in Northern Gresik. This tradition serves as an expression of fishermen’s gratitude for the sea’s bounty and as a form of respect for the ocean as a source of life. This study aims to examine the role of Petik Laut as a conservation strategy based on local wisdom in managing coastal resources. The research employs a qualitative approach using literature studies from various scientific journal sources and supporting documents. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings indicate that the Petik Laut tradition embodies ecological conservation values that can strengthen the collective awareness of coastal communities regarding the importance of marine preservation. Beyond its socio-cultural function, Petik Laut has the potential to become an effective community-based conservation model when integrated with modern approaches such as mangrove rehabilitation, coral reef transplantation, and ecosystem-based resource management. Thus, Petik Laut not only plays a role in preserving cultural heritage but also supports the sustainable management of coastal resources in a participatory manner.